Understanding why farmers adopt soil conservation tillage: A systematic review - Macson O. Ogieriakhi; Richard T. Woodward (Soil Security, 2022)
As soils across the globe continue to face problems of severe degradation and loss under current management practices, there is a great need to study soil conservation decisions such as conservation tillage (CST). In this paper, we consider the question of why farmers do and do not adopt CST by taking into account a wide variety of factors that impact farmers. Based on the literature, we argue that seven key factors enter the farmer's decision problem. These factors include farmers’ perceptions about soil health, risk, soil stewardship, the impact of adoption on profits, government payments, yield, and future access to land. We then review the literature to examine what has been learned about each of these factors. This sheds light on what we know about why farmers adopt CST, and what we do not know, thus identifying important areas for future research.